Thermoregulation in elite athletes - Reilly, T.; Drust, B.; Gregson, W. (Current Opinion in Clinical Nutrition and Metabolic Care, 2006)
Purpose of review: Exercise causes body temperature to rise and the resulting heat stored becomes a factor limiting exercise performance in hot conditions. Loss of heat by evaporative processes leads to hypohydration which itself can eventually impair performance. This review focuses on thermoregulatory and behavioural processes during sustained exercise in the heat.